Patient Satisfaction and Nipple-Areola Sensitivity After Bilateral Prophylactic Mastectomy and Immediate Implant Breast Reconstruction in a High Breast Cancer Risk Population: Nipple-Sparing Mastectomy Versus Skin-Sparing Mastectomy. Issue 2 (August 2016) - van Verschuer, Victorien M.T.; Mureau, Marc A.M.; Gopie, Jessica P.; Vos, Elvira L.; Verhoef, Cornelis; Menke-Pluijmers, Marian B.E.; Koppert, Linetta B.
Abstract : Background: Prophylactic skin-sparing mastectomy (SSM) and nipple-sparing mastectomy (NSM) both are associated with major risk reduction in women with high breast cancer risk. Skin-sparing mastectomy followed by nipple-areola complex (NAC) reconstruction is standard of care, but NSM is increasingly being performed. Preservation of the NAC in NSM may increase patient satisfaction. Therefore, we measured NAC sensitivity after NSM and compared patient satisfaction as well as body image after SSM with NSM. Methods: Women who underwent prophylactic bilateral SSM or NSM and immediate implant breast reconstruction between 2002 and 2012 were eligible. Patient satisfaction was assessed using the Breast-Q reconstruction questionnaire, body image using Hopwood's body image scale (BIS), and satisfaction with the (reconstructed) NAC using a study-specific questionnaire. In the NSM group, NAC sensitivity was assessed using Semmes Weinstein monofilaments with a 5-point scale and compared with NAC sensitivity in a nonoperated control group. Results: The SSM group comprised 25 women (50 SSMs) and the NSM group 20 women (39 NSMs). Median follow-up was 65 months in the SSM group compared with 27 months in the NSM group ( P < 0.01). In univariable analyses, Breast-Q scores were favorable in the SSM group compared with the NSM group with trends for higher "satisfaction with breasts" (66.2 vs 56.6; P = 0.06) and "satisfaction with outcome" (76.1 vs 61.5; P = 0.09). Mean BIS score of 7.1/30 in the SSM group and 9.3/30 in the NSM group ( P = 0.35). Adjusted for follow-up, there were no significant differences in Breast-Q scores, nor in BIS scores. Interestingly, satisfaction with the (reconstructed) NAC was similar after SSM and NSM. Nipple-areola complex sensitivity was lower in the NSM group (mean score, 1.9; 95% confidence interval, 1.5–2.3) compared with the control group (mean score, 4.7; 95% confidence interval, 4.6–4.9; P < 0.01). Conclusions: Breast-Q scores regarding satisfaction with breasts and overall outcome were in favor of the SSM group. Residual NAC sensitivity after NSM was low. This suggests that SSM followed by NAC reconstruction is a balanced alternative to NSM. We observed no significant differences in body image and NAC-specific satisfaction between the NSM and SSM groups.